In vitro fertilization outcomes In infertile women with adenomyosis - Tran, Ngoc Ha Giang; Le, Minh Tam (Tạp chí Y Dược Huế, 2023)
Objectives: This study aimed to investigate the efficacy of in vitro fertilization (IVF) in infertile patients with adenomyosis and to identify relevant factors. Subjects and methods: Retrospective descriptive study of infertile cases with adenomyosis who received IVF therapy and embryo transfer from November 2013 to October 2022 at the Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy Hospital, excluding cases of oocyte donation or surrogacy. The β-hCG test was examined two weeks following embryo transfer. Then, women with hCG positive test were followed the pregnancy at 6 weeks, 8 weeks, and 12 weeks, and examined some factors that influence the clinical outcome of pregnancy. Results: Among 61 cycles of IVF treatment for infertile patients with adenomyosis, the average number of retrieved oocytes was 10.9±6.6 oocytes. The percentage of mature oocytes was 82.7%, the fertilization rate was 79.5%, the implantation rate was 16.7%, the clinical pregnancy rate was 19.7%, the miscarriage rate was 6.6%, and the ongoing pregnancy rate was 13.1%. In the group with GnRH agonist administration before embryo transfer, the pregnancy rate was greater than in the group without therapy (29.2% vs. 13.5%), and th e pregnancy rate in the group with > 10 oocytes was higher than in the group with ≤ 10 oocytes (28.0% vs 13.5%). However, these differences were not statistically significant (with p > 0.05). The cut-off point of endometrial thickness on the day of hCG injection, 10.25 mm, had a sensitivity of 58.3%, a specificity of 81.6%, an area under the curve (AUC) of 75.6%, and a p-value of 0.006; the cut-off point of endometrial thickness on the day of embryo transfer, 9.75 mm, had an accuracy of 9.75 mm. sensitivity 75%, specificity 71.4%, AUC 78.50%, p = 0.002 for clinical pregnancy prognosis. Conclusion: The IVF treatment of infertile patients with adenomyosis remains challenging, and additional research is required to explain the influence of this disorder on IVF outcomes.